Unveiling Human Development Index Mediation on Consumption Dynamics - Rosdiana, Rosdiana; Majoo, Muhammad Yasin (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2024)
The research aims to explore the influence of household and government consumption expenditure on GRDP and its impact on HDI. Additionally, this study seeks to investigate the mediating role of HDI in the relationship between consumption expenditure and GRDP. The study utilizes data on Household Consumption Expenditures (HCE), Government Consumption Expenditures (GCE), Human Development Index (HDI), and Gross Regional Domestic Product (GRDP). The research population is all regions in North Maluku Province, totaling ten regions from 2013-2022. The sampling technique employs non-probability sampling with a census sampling method, resulting in a sample size equal to the population, which is 100 samples. The research adopts quantitative research methods, and the analysis techniques include SPSS and SmartPLS 4. The research findings indicate that Household Consumption Expenditures (HCE) significantly affect Gross Regional Domestic Product but do not impact the Human Development Index. Government Consumption Expenditures (GCE) do not significantly affect Gross Regional Domestic Product or the Human Development Index (HDI), and the Human Development Index (HDI) does not significantly influence Gross Regional Domestic Product (GRDP). Furthermore, HDI does not mediate the relationship between Household Consumption expenditure and Government Consumption expenditure on Gross Regional Domestic Product (GRDP).